Reception of Ketsubon-kyō (“Bloody Pond Sutra”) in Edo-period Japanese Pure Land Buddhism - Sobczyk, Małgorzata (Rocznik Orientalistyczny/Yearbook of Oriental Studies, 2026)
The Ketsubon-kyō (“Bloody Pond Sutra”), introduced to Japan through the fifteenth-century Tendai school, played a crucial role in shaping cross-sectarian Buddhist views on women’s salvation. Existing research primarily examines its general role in Buddhist eschatology, with school-specific studies focusing on Zen Sōtō and Pure Land (Jōdo‑shū) as exemplified by Shōyo Ganteki. This paper further explores its unique reception within the Pure Land strain of Buddhism from the 18th to 19th centuries. Two contrasting interpretations emerge: (1) The bloody pond (chinoike) originating in the sutra was understood as a realm exclusively for women who died in childbirth. (2) The sutra contributed to the eschatological idea of women’s impurity, reinforcing Hōnen’s view of their abandonment by buddhas. These perspectives highlight the Ketsubon-kyō’s influence on Pure Land Buddhism.